Global gray matter changes in posterior cortical atrophy: A serial imaging study - Lehmann, Manja (Alzheimers Dement, 2012)
BACKGROUND: Posterior cortical atrophy (PCA) is a neurodegenerative condition predominantly associated with Alzheimer’s disease (AD) pathology. Cross-sectional imaging studies have shown different atrophy patterns in PCA patients compared with typical amnestic Alzheimer’s disease (tAD) patients, with greatest atrophy commonly found in posterior regions in the PCA group, whereas in the tAD group, atrophy is most prominent in medial temporal lobe regions. However, differential longitudinal atrophy patterns are not well understood. METHODS: This study assessed longitudinal changes in brain and gray matter volumes in 17 PCA patients, 16 tAD patients, and 18 healthy control subjects. Both patient groups had symptom durations of approximately 5 years. RESULTS: Progressive gray matter losses in both PCA and tAD patients were relatively widespread throughout the cortex, compared with control subjects, and were not confined to areas related to initial symptomatology. A multivariate classification analysis revealed a statistically significant group separation between PCA and tAD patients, with 72.7% accuracy (P < .01). CONCLUSION: Progression from an initially focal presentation to a more global pattern suggests that these different clinical presentations of AD might converge pathologically over time.